TASK ANALYSIS IN ENGLISH TEXTBOOK AT ELEMENTARY SCHOOL IN THE FOURTH GRADE - Sarina Puspa; Iwan Jazadi (GLOBAL: Education Language and Humanity Journal, 2025)
This study investigates the nature and design of tasks in a fourth-grade English textbook used in Indonesian elementary schools, aiming to assess their alignment with curriculum objectives and language learning goals. Employing a descriptive qualitative method, the research utilizes Littlejohn’s (1998, 2011) Task Analysis Framework to examine 24 tasks across Units 1, 6, and 12 of the My Next Word textbook. The analysis reveals that tasks predominantly require scripted responses, emphasize form-meaning relationships, and rely on low-level cognitive operations such as repetition and recall. Interaction is mostly individual or whole-class based, with minimal peer collaboration or opportunities for spontaneous language use. Content is largely sourced from the textbook itself, focusing on controlled input and output without contextual or communicative variation. These findings highlight a strong reliance on input-driven activities with limited output demands, raising concerns about the textbook’s capacity to support communicative competence and higher-order language skills. The study underscores the importance of task variety, cognitive challenge, and interactional engagement in textbook design to better support the holistic development of learners’ English proficiency in primary education settings.